Primary liposarcoma of the heart. Issue 729 (July 1986) - Cyjon, A.; Rakowsky, E.; Mor, C.; Barzilay, J.
Abstract : A rare form of primary heart tumour, a liposarcoma, is reported. A discussion of diagnosis and modalities of treatment of primary heart sarcomas is presented.